1983
DOI: 10.1071/wr9830435
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Abundance of Kangaroos in relation to Environment in Western Australia

Abstract: Red and western grey kangaroos were surveyed from the air in Western Australia during the winter of 1981. The area covered, 1 528 000 km2 or 61% of the State, excluded only the Kimberleys in the north and the Gibson and Great Sandy Deserts of the interior. Hence almost all kangaroo range within the State was surveyed, to provide an estimate of 980 000 reds and 436 000 greys. Densities were much lower than those of the eastern States. Red kangaroos were most abundant in mulga shrubland, chenopod shrubland and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…A partial explanation for this relationship may be the tendency in Australia for grazing properties to be located in more productive areas and conservation reserves in less productive areas (Pressey 1995). Short et al (1983) similarly found that red kangaroos were most abundant on sheep-grazing properties, and less abundant on vacant crown land in Western Australia. In Queensland, high abundances of antilopine wallaroos occurred in the Einasleigh Uplands bioregion, which supports relatively intense cattle grazing, and provides a large number of artificial watering points.…”
Section: Niche Variation In Marsupial Herbivoresmentioning
confidence: 87%
“…A partial explanation for this relationship may be the tendency in Australia for grazing properties to be located in more productive areas and conservation reserves in less productive areas (Pressey 1995). Short et al (1983) similarly found that red kangaroos were most abundant on sheep-grazing properties, and less abundant on vacant crown land in Western Australia. In Queensland, high abundances of antilopine wallaroos occurred in the Einasleigh Uplands bioregion, which supports relatively intense cattle grazing, and provides a large number of artificial watering points.…”
Section: Niche Variation In Marsupial Herbivoresmentioning
confidence: 87%
“…This proportion increases under dry conditions (Oliver 1986; Croft 1991). Mobile animals have been found to make short‐range (25–30 km) and long‐range (> 100 km) movements (Bailey 1971; Newsome 1975; Denny 1982; Short et al 1983; Croft 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the largest members of this assemblage, species of red and gray kangaroos, are scattered across the Australian landscape from the east to west coasts (Short et al 1983). Gray kangaroos are classified into western and eastern forms, Macropus fuliginosus and eastern M. giganteus, respectively, with a zone of sympatry between the two species located in portions of the states of Victoria, New South Wales, and Queensland (Caughley et al 1984;Neaves et al 2010).…”
Section: Marsupial Divergence-with-gene-flow: Interspecific Mating Inmentioning
confidence: 99%